Evaluating Social Housing Suitability in Oasis Cities Using GIS-Based Multi-Criteria Decision Analysis: A Case Study of Bou Saada, Algeria - Kaourane Mohamed; Redjem Ali; Nouibat Brahim (International Journal of Computational and Experimental Science and Engineering, 2025)
This research presents a comprehensive assessment of habitat suitability in oasis environments by integrating advanced spatial analysis with multi-criteria decision-making methods. Oasis settings face specific climatic, cultural and spatial constraints that require analytical frameworks capable of capturing local complexity. To address this, the study uses a combined geographic information system (GIS) and analytic hierarchy process (AHP) approach to evaluate social housing suitability in three neighborhoods in Bou Saada, Algeria: the traditional old town (Kasser), the standardized 270 social housing development, and the newly planned AADL neighborhood.The analysis is structured around a multi-criteria framework that includes four key dimensions: environmental-climatic factors (34.7%), socio-cultural criteria (29.8%), functional and design aspects (20.3%) and economic-sustainability considerations (15.2%). Criterion weights were obtained using the AHP method, with consistency ratio verification (CR < 0.10) to ensure reliable pairwise comparisons. The results show significant variations in suitability between districts. The Old Town received the highest score (8.5/10), which reflects strong climate adaptability, cultural continuity and community cohesion. The AADL area was second (6.4/10), demonstrating moderate but better performance. In contrast, 270 social housing sector showed the lowest suitability (4.4/10), which indicates significant design limitations and weak contextual integration.These findings confirm that traditional urban forms provide inherent adaptive advantages in oasis environments. In addition to demonstrating the effectiveness of GIS-AHP integration at the neighborhood scale, the study provides practical insights for planners and policy makers engaged in developing climate-responsive, culture-based housing strategies for arid regions.